Canang Sari sebagai Sarana Ritual Masyarakat Hindu Bali di Desa Sedahan Jaya Sukadana Kayong Utara Kalimantan Barat - Duta Valentino; Arkanudin Arkanudin; Adi Suryadi; Efriani Efriani (Ideas Publishing, 2023)
Canang Sari as a means of ritual for the Balinese Hindu community who are outside the island of Bali is still maintained even though the materials used are different. The purpose of this study is to reveal Canang Sari as a place for offerings to complete religious rituals in the Balinese community of Sedahan Jaya Sukadana Kayong Utara village. To obtain information, descriptive methods were used with observation techniques, interviews and documentation studies, then analyzed qualitatively simultaneously, namely field notes, gathering information, presenting information and drawing conclusions. The results of the study revealed that they still maintain the tradition of offering canangsari in religious ceremonies both in front of the house and in the rice fields. It is believed to bring blessings and abundant crops